Effect of melatonin on tau aggregation and tau-mediated cell surface morphology - Das, Rashmi; Balmik, Abhishek Ankur; Chinnathambi, Subashchandrabose (International Journal of Biological Macromolecules, 2020)
Aggregation of Microtubule-associated protein Tau and its deposition in the form of neurofibrillary tangles (NFTs) is one of the pathological hallmarks of Alzheimer's disease (AD). Tau aggregation inhibition has been targeted in various studies including natural compounds and synthetic small molecules. Here, we have studied neurohormone- Melatonin against in vitro Tau aggregation and observed its effect on membrane topology, tubulin network and Tau phosphorylation in Neuro2A and N9 cell lines. The aggregation and conformation of Tau was determined by ThT fluorescence and CD spectroscopy respectively. The morphology of Tau aggregates in presence and absence of Melatonin was studied by transmission electron microscopy. Melatonin was found to reduce the formation of higher order oligomeric structures without affecting the overall aggregation kinetics of Tau. Melatonin also modulates and helps to maintain membrane morphology, independent on tubulin network as evidenced by FE-SEM and immunofluorescence analysis. Overall, Melatonin administration shows mild anti-aggregation and cytoprotective effects. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Alzheimer's disease; Cell surface morphology; melatonin; Paired helical filaments; tau protein; Tauopathies

EGCG impedes human Tau aggregation and interacts with Tau - Sonawane, Shweta Kishor; Chidambaram, Hariharakrishnan; Boral, Debjyoti; Gorantla, Nalini Vijay; Balmik, Abhishek Ankur; Dangi, Abha; Ramasamy, Sureshkumar; Marelli, Udaya Kiran; Chinnathambi, Subashchandrabose (Scientific Reports, 2020)
Tau aggregation and accumulation is a key event in the pathogenesis of Alzheimer's disease. Inhibition of Tau aggregation is therefore a potential therapeutic strategy to ameliorate the disease. Phytochemicals are being highlighted as potential aggregation inhibitors. Epigallocatechin-3-gallate (EGCG) is an active phytochemical of green tea that has shown its potency against various diseases including aggregation inhibition of repeat Tau. The potency of EGCG in altering the PHF assembly of full-length human Tau has not been fully explored. By various biophysical and biochemical analyses like ThS fluorescence assay, MALDI-TOF analysis and Isothermal Titration Calorimetry, we demonstrate dual effect of EGCG on aggregation inhibition and disassembly of full-length Tau and their binding affinity. The IC50 for Tau aggregation by EGCG was found to be 64.2 mu M.

Epigallocatechin-3-gallate modulates tau post-translational modifications and cytoskeletal network - Sonawane, Shweta Kishor; Chinnathambi, Subashchandrabose (Oncotarget, 2021)
BACKGROUND: Alzheimer's disease is a type of dementia denoted by progressive neuronal death due to the accumulation of proteinaceous aggregates of Tau. Post-translational modifications like hyperphosphorylation, truncation, glycation, etc. play a pivotal role in Tau pathogenesis. Glycation of Tau aids in paired helical filament formation and abates its microtubule-binding function. The chemical modulators of Tau PTMs, such as kinase inhibitors and antibody-based therapeutics, have been developed, but natural compounds, as modulators of Tau PTMs are not much explored. MATERIALS AND METHODS: We applied biophysical and biochemical techniques like fluorescence kinetics, oligomerization analysis and transmission electron microscopy to investigate the impact of EGCG on Tau glycation in vitro. The effect of glycation on cytoskeleton instability and its EGCG-mediated rescue were studied by immunofluorescence microscopy in neuroblastoma cells. RESULTS: EGCG inhibited methyl glyoxal (MG)-induced Tau glycation in vitro. EGCG potently inhibited MG-induced advanced glycation endproducts formation in neuroblastoma cells as well modulated the localization of AT100 phosphorylated Tau in the cells. In addition to preventing the glycation, EGCG enhanced actin-rich neuritic extensions and rescued actin and tubulin cytoskeleton severely disrupted by MG. EGCG maintained the integrity of the Microtubule Organizing Center (MTOC) stabilized microtubules by Microtubule-associated protein RP/EB family member 1 (EB1). CONCLUSIONS: We report EGCG, a green tea polyphenol, as a modulator of in vitro methylglyoxal-induced Tau glycation and its impact on reducing advanced glycation end products in neuroblastoma cells. We unravel unprecedented function of EGCG in remodeling neuronal cytoskeletal integrity.
Keywords: Alzheimer’s disease; tau glycation; Tau glycation inhibition; tau protein; Tau PTMs

Extracellular HDAC6 ZnF UBP domain modulates the actin network and post-translational modifications of Tau - Balmik, Abhishek Ankur; Sonawane, Shweta Kishor; Chinnathambi, Subashchandrabose (Cell Communication and Signaling, 2021)
Background: Microtubule-associated protein Tau undergoes aggregation in Alzheimer`s disease (AD) and a group of other related diseases collectively known as Tauopathies. In AD, Tau forms aggregates, which are deposited intracellularly as neurofibrillary tangles. Histone deacetylase-6 (HDAC6) plays an important role in aggresome formation, where it recruits polyubiquitinated aggregates to the motor protein dynein. Methods: Here, we have studied the effects of HDAC6 ZnF UBP on Tau phosphorylation, ApoE localization, GSK-3 beta regulation and cytoskeletal organization in neuronal cells by immunocytochemical analysis. This analysis reveals that the cell exposure to the UBP-type zinc finger domain of HDAC6 (HDAC6 ZnF UBP) can modulate Tau phosphorylation and actin cytoskeleton organization. Results: HDAC6 ZnF UBP treatment to cells did not affect their viability and resulted in enhanced neurite extension and formation of structures similar to podosomes, lamellipodia and podonuts suggesting the role of this domain in actin re-organization. Also, HDAC6 ZnF UBP treatment caused increase in nuclear localization of ApoE and tubulin localization in microtubule organizing centre (MTOC). Therefore, our studies suggest the regulatory role of this domain in different aspects of neurodegenerative diseases. Upon HDAC6 ZnF UBP treatment, inactive phosphorylated form of GSK-3 beta increases without any change in total GSK-3 beta level. Conclusions: HDAC6 ZnF UBP was found to be involved in cytoskeletal re-organization by modulating actin dynamics and tubulin localization. Overall, our study suggests that ZnF domain of HDAC6 performs various regulatory functions apart from its classical function in aggresome formation in protein misfolding diseases.
Keywords: Actin; Cytoskeleton; HDAC6; Microtubule; neurodegeneration; Phosphorylation; Podonut; Podosomes; Tau; Tauopathies